Effect of different curing systems on cell structure, mechanical properties and aging resistance of nitrile butadiene rubber foam coating with liquid compounds. (June 2014) - Zheng, N.; Qiu, Z. M.; Liu, J.; Wang, X. M.; He, W. J.; Xiao, J. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Gaskets made of acrylonitrile butadiene rubber (NBR) coating and metal plate were one of the classified seals used in automotive engine. In the present study, NBR foam–metal composite gaskets were prepared by liquid NBR overlain metal plate. The foam coating was thinner and more uniform compared with solid rubber forms usually used. Two different curing systems of dicumyl peroxide (DCP) system and a combined system of sulphur with DCP (S/DCP system) were investigated for curing NBR foam coating. The effects of curing system and agent content on cell structure, mechanical properties and resistance to fluid and heat of NBR foam, and the interfacial adhesion between NBR foam coating and metal plate, were examined. It was found that the S/DCP system gave NBR foam coating with bigger cell size, higher porosity and cross-link density compared with the DCP system. Furthermore, the S/DCP system had better tensile property and played a better role in the protection of the gasket seals against fuel B and hot air.